Implementasi Media Corong Berhitung Dalam Pembelajaran Matematika (Perkalian) Kelas II di SD Negeri 3 Gesikan Tulungagung - Yunita Desi Dwi Jayanti (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The purpose of this research study is the application of counting funnel media to make it easier for students to understand multiplication lessons. This research is descriptive qualitative research by describing all the results of there search. Data collection techniques used by researchers are observation, interviews, and documentation. The subjects of this study were grade II SDN 3 Gesikan with the number of students as many as 35. The results of the study, namely the implementation of counting funnel media in mathematics learning (multiplication) in class II, had been well implemented. this media can help teachers and students in the process of learning mathematics especially multiplication lessons. The teacher's steps to apply are appropriate. During the use of media students pay attention, besides that students also understand what is conveyed by the teacher easily. The conclusion that the implementation of funnel media counting has been done well and smoothly. This media has helped the teacher to deliver the material and students to understand the material. This media is good to use mathematics learning especially multiplication material. in a simple way can lure students to pay attention to student focus.